Analisis Penggunaan Google Classroom Sebagai Media Pembelajaran Saat Pandemi Covid-19 Terhadap Motivasi Belajar Siswa - Kadek Ayu Astiti; Vinsensius Lantik; Yenji Revita Tulle (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2023)
This study analyzes the use of google classroom as a learning medium during the covid-19 pandemic on learning motivation. Research objectives to find out the use af google classroom as a learning medium during covid-19 and student learning motivation after using google classroom as a learning medium during covid-19. This research includes qualitative descriptive research. The research subjects were 1 physics teacher and 5 students of SMA Negeri 5 kupang. Data collection methods include observation, interviews and documentation. The results of this study concluded that the use of google classroom as a learning medium during the covid-19 pandemic on student learning motivation has gone well. Tis can be proven that the use of google classroom can increase the desire, attraction, motivation, and also arouse students desire to learn. Improving the quality of learning can be seen through increasing teaching and learning activities and improving the final of results of student acquisition.